Rostral Middle Frontal Volumetric Differences in Bipolar Offspring versus Community Controls Offspring (2019)
ABSTRACT: Neuroanatomical findings in the anterior limbic network in bipolar disorder (BD) adults have not been replicated in other populations such as bipolar offspring (BO). The aim of this study was to compare some brain areas volumes between BO with and without a lifetime affective disorder (AD) to a group of community control offspring (CCO). Methods: A descriptive observational cross-sectional study was carried out, with multiple comparison groups. Seven subjects (11-17 years old) from the BO with AD group were compared to seven subjects from the BO without AD group and seven subjects from the CCO group (match by age, gender and Tanner stage). Magnetic resonance imaging was performed with a Philips 3 Teslas device and volumetric segmentation was performed with the Freesurfer image analysis suite. Results: A larger size was found in the right middle frontal rostral region in the BO with AD group compared to the other two groups (p = 0.041). A higher volume was also found in BO with AD group in the left pars opercularis (Cohen d = 0.63) and in the right cingulate isthmus (d = 0.53) when compared with BO without AD group, and in the right hippocampus (d = 0.53) when compared to CCO group. A smaller volume was found in the BO without AD group versus CCO group in the left anterior caudate (d = 0.6). The BO groups (with and without AD) compared to CCO have a higher volume in the right frontal pole (d = 0.52). These volumetric differences can be attributed to the condition of BO with AD.